Infliximab ameliorates tumor necrosis factor-alpha-induced insulin resistance by attenuating PTP1B activation in 3T3L1 adipocytes in vitro - Méndez-García, Lucia A.; Trejo-Millán, Fernanda; Martínez-Reyes, Camilo P.; Manjarrez-Reyna, Aarón N.; Esquivel-Velázquez, Marcela; Melendez-Mier, Guillermo; Islas-Andrade, Sergio; Rojas-Bernabé, Araceli; Kzhyshkowska, Julia; Escobedo, Galileo (Scandinavian journal of immunology, 2018)
Insulin resistance is the inability to respond to insulin and is considered a key pathophysiological factor in the development of type 2 diabetes. Tumor necrosis factor-alpha (TNF-alpha) can directly contribute to insulin resistance by disrupting the insulin signalling pathway via protein-tyrosine phosphatase 1B (PTP1B) activation, especially in adipocytes. Infliximab (Remicade® ) is a TNF-alpha-neutralizing antibody that has not been fully studied in insulin resistance. We investigated the effect of infliximab on TNF-alpha-induced insulin resistance in 3T3L1 adipocytes in vitro, and examined the possible molecular mechanisms involved. Once differentiated, adipocytes were cultured with 5 mmol L-1 2-deoxy-D-glucose-3 H and stimulated twice with 2 μmol L-1 insulin, in the presence or absence of 5 ng/mL TNF-alpha and/or 10 ng/mL infliximab. Glucose uptake was measured every 20 minutes for 2 hour, and phosphorylated forms of insulin receptor (IR), insulin receptor substrate-2 (IRS-2), protein kinase B (AKT) and PTP1B were determined by Western blotting. TNF-alpha-treated adipocytes showed a significant 64% decrease in insulin-stimulated glucose uptake as compared with control cells, whereas infliximab reversed TNF-alpha actions by significantly improving glucose incorporation. Although IR phosphorylation remained unaltered, TNF-alpha was able to increase PTP1B activation and decrease phosphorylation of IRS-2 and AKT. Notably, infliximab restored phosphorylation of IRS-2 and AKT by attenuating PTP1B activation. This work demonstrates for the first time that infliximab ameliorates TNF-alpha-induced insulin resistance in 3T3L1 adipocytes in vitro by restoring the insulin signalling pathway via PTP1B inhibition. Further clinical research is needed to determine the potential benefit of using infliximab for treating insulin resistance in patients.